Novel thermally self-crosslinkable diarylfluorene-based copolymers for efficient and stable blue light-emitting diodes. Issue 27 (19th June 2020) - Liu, Alei; Liu, Zhe; Lin, Hong; Tang, Wenwei; Lin, Zesen; Zhang, Weina; Qi, Zhengjian; Gu, Xiaofei; Mo, Yueqi; Hou, Lintao
Abstract : A new series of thermally initiated self-crosslinkable diarylfluorene-based copolymers have been reasonably designed and successfully synthesized, aiming to improve both efficiency and stability of blue light-emitting diodes. Abstract : A new series of thermally initiated self-crosslinkable diarylfluorene-based copolymers have been reasonably designed and successfully synthesized, aiming to improve both efficiency and stability of blue light-emitting diodes. The crosslinking groups in side chains endow these copolymers with excellent solvent resistance and anti-oxidation abilities, as verified through Raman and UV-vis absorption as well as variable temperature photoluminescence spectra. The surface roughness of the thermal self-crosslinking copolymer film is almost unchanged with a low value of 0.73 nm, compared to a roughness of 0.68 nm for the original film without crosslinking. The modulation of the energy levels of copolymers with/without a crosslinking reaction is analyzed through computations and experiments. The up-shifted highest occupied molecular orbital (HOMO) energy level of the thermal self-crosslinking copolymer film by about 0.1 eV in comparison with that of the uncrosslinked copolymer film is conducive to the establishment of a better pathway for hole injection from the anode. In the end, a high external quantum efficiency of 4.29% with a maximum brightness of 7491 cd m −2 is achieved for the optimized blue polymer light-emitting diode (PLED) with the use of a thermal crosslinking copolymer emitter, which is the highest efficiency reported so far in the field of self-crosslinking blue fluorescent emitters. This work demonstrates that the introduction of self-crosslinkable side-chain units far from the blue polymer backbone is a very promising strategy for developing highly efficient and stable blue PLEDs.